SIDE EFFECTS OF INTRAVENOUS GANCICLOVIR AND COMBINATION OF INTRAVENOUS GANCICLOVIR-ORAL VALGANCICLOVIR IN PEDIATRIC PATIENTS WITH CYTOMEGALOVIRUS INFECTION - I WAYAN ANDREW HANDISURYA; NELLY AMALIA RISAN; DWI PRASETYO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Intravenous ganciclovir and oral valganciclovir are known to have severe side effects against hematopoiesis and kidney function. This study aims to look for these side effects in pediatric patients with cytomegalovirus (CMV) infection treated with ganciclovir or a combination regimen of both in Hasan Sadikin General Hospital, a tertiary care center in West Java, Indonesia. Methods: This was a cross-sectional study using medical records and laboratory examination data from pediatric patients with CMV infection who received ganciclovir of 6 mg/kg twice a day, valganciclovir of 16 mg/kg twice a day, or a combination of both in Hasan Sadikin General Hospital from January 2015 to January 2019. Differences before and after therapy were analyzed to look for any side effects in each regimen and duration of therapy. Results: Out of 115 patients, there were 53 subjects who met the research criteria. Majority of the subjects used a combination regimen (n=29, 55%) for 6 weeks (n=36, 68%). There was no statistically significant difference (p>0.05) in the incidence of anemia, neutropenia, thrombocytopenia, increase in creatinine serum, or increase in blood urea nitrogen for different regimen or duration of therapy. Conclusion: No side effects were found to be related with therapeutic regimen or duration of therapy in pediatric patients with CMV infection in this study.